A place for climate in a time of capitalist crisis? A case study of low-carbon urban policy making in Liverpool, England. Issue 2 (March 2020) - Nurse, Alexander; North, Peter
Abstract : This paper draws upon regulationist perspectives to explore the rationales which inform low-carbon economic development at the city level. This work is developed through a case study of low-carbon policy making in Liverpool, UK. The paper identifies conflict between those who argue for deeper engagement with the emerging low-carbon policy domain, and others who remain committed to maintaining existing patterns of growth. The paper argues that regulationist-inspired perspectives particularly help understand places where the transition to a low-carbon economy can falter in the face of competing agendas such as reigniting growth and coping with austerity.